Formation and development of methodology and philosophy of education - Лаута, О. Д. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
In the article the features of formation and development of the methodology and philosophy of education Done historical and philosophical analysis of the origin of the philosophy of education. Since Socrates, philosophy questioned the «obvious» critically rethink existing algorithms thinking , constantly expanding its scope and range of products. Thus, it is the philosophy of the perceived crisis of education formed new ideals of education, new ideas about the process of learning and education and so on. Today, the substance of the problem is trying to understand the philosophy of education. Аnalyzed the formation of new ideals of education, new ideas about the process of learning and education. We characterize modern philosophies of education methodology and basic principles of the existence of modern education.The attention to new philosophical concepts of education. Characteristic of modern concepts of education philosophy is the focus on criticism of the classical type of education, which started the «new philosophers of science»–Т. Kuhn, I. Lakatos, P. Feyerabend. Modern philosophies demonstrate full methodology dominant orientation and basic principles of the existence of modern education: humanistic principle, the principle of differentiation and the principle of integration, based on these principles can be a concept of education that would be the epitome of modern achievements in philosophy of education.